CLIENTELISM AND THE EROSION OF LEGISLATIVE OVERSIGHT: EXAMINING THE HOUSE OF REPRESENTATIVE (DEWAN PERWAKILAN RAKYAT, DPR) ROLE UNDER PRESIDENT JOKO WIDODO (2014–2024) - Andika Kurniawan, Muhammad Tri; Devi, Suseela Chandra (Universitas Padjadjaran, 2025)
This article investigates the weakening of legislative oversight by The House of (Dewan Perwakilan Rakyat, DPR) during President Joko Widodo’s tenure from 2014 to 2024. Despite the expanded constitutional authority granted to the DPR following the 1998 political reforms, the quality of oversight function has diminished markedly in the Jokowi era. Drawing on theoretical and empirical literature, the article argues that this erosion is not solely the result of institutional shortcomings or inadequate reform, but is primarily driven by pervasive clientelistic relationships between the president and party elites. Such clientelism entrenches political patronage, enabling the executive to exert significant influence over legislative behavior and undermining the DPR’s independence. This study uses a qualitative, interpretivist approach, employing in-depth interviews, observation, and literature review within real social contexts. This study aims to provide a critical assessment of how clientelism has reshaped the balance of power between executive and legislature.